From policy to practice: a comparative overview of policies and interventions to curb street gangs in both the international and local contexts - Petrus, T. S. (Acta criminologica, 2017)
The focus of this article is to provide a comparative overview of the policies and intervention strategies that international countries have affected to curb street gangs, as well as those that South Africa have employed to address the street gang challenge in affected areas. The author specifically attempts to determine what, if any, lessons can be learnt in the South African context from successful, or even unsuccessful, efforts to curb gangs and their activities in regions such as North and Central America, among others. It is argued that South African policymakers would do well to heed the lessons from international gang prevention efforts, in order to formulate policies and interventions that would be effective rather than exacerbate the problem(s) associated with street gangs.